The Influence of Leadership, Work Motivation, and Compensation on Employee Performance through Job Satisfaction as an Intervening Variable at Bank Syariah Indonesia KC Gatot Subroto Jambi - Fitria, Savira; Mubyarto, Novi; Nengsih, Titin Agustin; Anita, Efni; Rahma, Sri; Munsarida (International Journal of Economics (IJEC), 2024)
This study examines the direct and indirect effects of the variables of Leadership, Work Motivation, and Compensation on Employee Performance through Job Satisfaction as an intervening variable. This research is a quantitative study using the Total Sampling method with 45 respondents. Data analysis is conducted using the Structural Equation Modeling (SEM) analysis with Smart-PLS computer program. The results of this study are as follows: 1) Leadership has a positive and significant effect on Job Satisfaction 2) Work Motivation does not have a significant effect on Job Satisfaction 3) Compensation has a positive and significant effect on Job Satisfaction 4) Leadership has a positive and significant effect on Employee Performance 5) Work Motivation has a positive and significant effect on Employee Performance 6) Compensation does not have a significant effect on Job Satisfaction 7) Job Satisfaction has a positive and significant effect on Employee Performance 8) Job Satisfaction is able to influence the relationship between Leadership and Employee Performance 9) Job Satisfaction is not able to influence the relationship between Work Motivation and Employee Performance 10) Job Satisfaction is able to influence the relationship between Compensation and Employee Performance.